Topological–chiral magnetic interactions driven by emergent orbital magnetism - S. Grytsiuk (Nature Portfolio, 2020)
The motion of electrons in a complex magnetic background may generate novel magnetic interactions. Here, Grytsiuk et al. report that a peculiar orbital motion of electrons in response to a non-coplanarity of neighbouring spins leads to a topological orbital moment, which further gives rise to a new class of magnetic interactions.